2016
DOI: 10.1016/j.ejmech.2016.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of novel serotonin 4 receptor radiotracers for single photon emission computed tomography

Abstract: Despite its implication in several physiological and pathological processes the serotonin subtype-4 receptor (5-HT4R) has seen limited effort for the development of radiolabeling agent especially concerning single photon emission computed tomography (SPECT). Bearing an ester function, the available ligands are rapidly susceptible to hydrolysis which limits their use in vivo. In this study the synthesis of iodinated benzamide and ketone analogs were described. Their affinity for the 5-HT4R and their lipophilici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Direct electrophilic aromatic substitution is a typical process to perform radioiodination of aromatic molecules . Generally, this strategy exhibits low regioselectivity unless there has been careful choice of starting compound.…”
Section: Radioiodination Of Csp 2 Centersmentioning
confidence: 99%
“…Direct electrophilic aromatic substitution is a typical process to perform radioiodination of aromatic molecules . Generally, this strategy exhibits low regioselectivity unless there has been careful choice of starting compound.…”
Section: Radioiodination Of Csp 2 Centersmentioning
confidence: 99%
“…(1-Butylpiperidin-4-yl)methanamine ( 10b = 11b ) and (1-propylpiperidin-4-yl)methanamine ( 12b ) were prepared according to the literature from piperidine-4-carboxamide by alkylation followed by reduction [56,57]. The preparation of target products 10–12 was conducted as follows: the commercially available 4-aminophenol was treated with alkyl chloroformates (R 1 = Me, Bu) followed by epichlorohydrin addition to give requisite methyl [4-(oxiran-2-ylmethoxy)phenyl]carbamate ( 10a = 12a ) and butyl [4-(oxiran-2-ylmethoxy)phenyl]carbamate ( 11a ) [58].…”
Section: Resultsmentioning
confidence: 99%
“…A solution of the corresponding (1-alkylpiperidin-4-yl)methanamine 10b–12b [56,57] (11.60 mmol) in methanol (30 mL) was added dropwise to a solution of the appropriate alkyl [4-(oxiran-2-ylmethoxy)phenyl] carbamate 10a–12a [58] (9.00 mmol) in methanol (40 mL). The resulting mixture was left stirring for two days at ambient temperature and then concentrated under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…in methanol (40 ml). After 15 minutes of additional stirring, the reaction mixture was removed from the ice bath and stirred at 25 °C for 24 h. [33][34][35] The progression of the reaction was examined by TLC (mobile phase used: 10% methanol in chloroform) which showed that the desired products were formed after 24 h of stirring at 25 °C. The reaction mixture was added to cold diethyl ether.…”
Section: Chemistrymentioning
confidence: 99%